2009
DOI: 10.1002/jrs.2411
|View full text |Cite
|
Sign up to set email alerts
|

Parabolic mirror‐assisted tip‐enhanced spectroscopic imaging for non‐transparent materials

Abstract: A versatile and efficient tip-enhanced spectroscopic imaging technique based on a parabolic mirror (PM) assisted near-field optical microscope is demonstrated. The replacement of the conventional objective lens with a parabolic mirror allows the non-restricted investigation of sample materials regarding their opacity. In addition, an improved signal collection efficiency and effective excitation of the longitudinal plasmonic oscillation in the tip apex are obtained. The capabilities of PM-assisted tip-enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 30 publications
0
79
0
1
Order By: Relevance
“…Therefore, the TERS measurements require an inert environment such as nitrogen or argon. Furthermore, in TERS spectra from these samples a broad PL band such as that from P3HT may overlap with the Raman bands; therefore, a reliable fitting procedure is required to accurately deconvolute the Raman and PL bands in order to measure their intensities [61].…”
Section: Organic Solar-cellsmentioning
confidence: 99%
“…Therefore, the TERS measurements require an inert environment such as nitrogen or argon. Furthermore, in TERS spectra from these samples a broad PL band such as that from P3HT may overlap with the Raman bands; therefore, a reliable fitting procedure is required to accurately deconvolute the Raman and PL bands in order to measure their intensities [61].…”
Section: Organic Solar-cellsmentioning
confidence: 99%
“…The parabolic mirror based near-field optical microscope was already described previously [9,14,15]. A radially polarized donut beam [5] of a helium-neon laser (λ = 632.8 nm) is focused on the sample surface.…”
Section: Methodsmentioning
confidence: 99%
“…This tip is the crucial element that turns TERS into a highly versatile combination of Raman spectroscopy and topographical scanning probe microscopy. Atomic force microscopy (AFM) [2], scanning tunnelling microscopy (STM) [8] and shear force microscopy [11,15] have all been employed successfully. The optical resolution obtained in TERS is determined by the size of the tip apex [7] and optical resolutions of 10-20 nm are achievable, a range far below the Rayleigh limit of conventional optical microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Domains of polystyrene and polyisoprene were identified in a thin film using aromatic ring stretches at 1002 cm -1 and 1602 cm -1 to identify polystyrene and carbon double bond vibrations at 1664 cm -1 to denote polyisoprene. Poly-3-hexyl-thiophene (P3HT) and phenyl-C61-butyric acid methyl ester (PCBM), a commonly used blend for solar cells, showed thiophene bands at 1450 cm -1 ; however, the authors reported no observable signal form PCBM [106]. Temporal signal variations in the TERS signal from PEDOT/PSS films suggested thermal diffusion within the blend [99].…”
Section: Organic Polymers and Moleculesmentioning
confidence: 99%